Baked Egg Oral Immunotherapy (OIT) Induces Significant Immune Modulation in Baked Egg Reactive Subjects and Induces Tolerance to Lightly Cooked Egg - White, Hannah; Clark, April; Dougherty, Irene; Brown, L. Steven; Arneson, Amy; Crain, Maria; Parrish, Christopher P.; Bird, J. Andrew (Journal of allergy and clinical immunology, 2018)
Methods EAC reacting to BE containing high dose (3.8g) egg protein or with ovomucoid (OM)-IgE>50kU/L were included. Egg white (EW)-, OM-, and ovalbumin (OA)-IgE and IgG4, and EW skin prick test (SPT) were obtained at 0, 6, 12, 18 and 24 months.